Công nghệ thực tế ảo tăng cường có phải là một công cụ hiệu quả trong bối cảnh hiện nay không? Vai trò của sự trải nghiệm đắm chìm - Võ Kim, Nhạn (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
This study aims to construct and test the research model on the relationship between customer immersion on behavioral intention regarding augmented reality applications (AR apps). Moreover, attitude toward AR apps mediates the relationship between customer immersion and behavioral intention regarding AR apps. In addition, privacy concern is considered as moderating variable of the relationship between immersive experience and behavioral intention regarding AR apps. The partial least square structural equation modeling (PLS-SEM) was applied on 332 samples to test the hypotheses. The testing results indicated that all proposed hypotheses were supported. Thus, this study has some important contributions in both academic and practical ways in using AR applications to provide added information and value for customers.
Keywords: Immersive experience; Attitude; Behavioral intention; Privacy concern; Augmented reality; AR apps